THE INFLUENCE OF HUMAN RESOURCE QUALITY, PRODUCT INNOVATION AND MARKETING STRATEGY ON THE SUSTAINABILITY OF MSME BUSINESSES IN JEMBER REGENCY THROUGH INFORMATION TECHNOLOGY - Muhammad Syaifullah; Haris Hermawan; Amalina Maryam Zakiyyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
MSMEs in Jember Regency face sustainability challenges amid fierce competition and lack of digitalization. This research aims to analyze the influence of human resource quality, product innovation, and marketing strategies on the sustainability of MSME businesses through information technology mediation. Using an explanatory research approach with the population of Jember MSME actors, samples were taken through probability sampling and analyzed with Structural Equation Modeling-PLS via SmartPLS. The results show that all independent variables have a positive and significant effect on business sustainability, both directly and indirectly through effective information technology mediation. The model explains the variation in sustainability well, confirming the crucial role of the quality of competent human resources, creative product innovation, and adaptive marketing strategies in driving the adoption of e-commerce and digital marketing. The findings support a consistent literature while filling research gaps from previous contradictory studies. The practical implications of recommending digital HR training through PLUT KUMKM Jember, Canva-based innovation workshops, and TikTok live selling strategies; theoretically suggests the development of a hybrid TAM-DOI model for the context of East Java MSMEs for sustainable transformation